Barrier Island Suite : Poems - Dunkelberg, Kendall (Book collections on Project MUSE., 2016)
The poems of Barrier island suite are inspired by the life, art, and writings of Walter Inglis Anderson, who spent much of his adult life exploring the barrier islands of Mississippi, sketching and painting their flora and fauna, and chronicling his adventures in numerous logs. The islands form a liminal space between the land and sea, between nature and culture, between madness and conformity. Elements of the Anderson's life, including his travels, his struggles with mental illness, and his murals at Oldfields, the Ocean Springs Public School and Community Center, and the cottage at Shearwater Pottery are also incorporated. (From ECIP data view summary.).